2020
DOI: 10.1007/s42991-020-00083-1
|View full text |Cite
|
Sign up to set email alerts
|

Guest or pest? Spatio-temporal occurrence and effects on soil and vegetation of the wild boar on Elba island

Abstract: Where allochthonous large mammals, such as the wild boars, occur in high density, human-wildlife conflicts may arise. Thus, assessing their spatio-temporal patterns is paramount to their management. We studied the wild boars on Elba island, Italy, where they have been introduced and are perceived as pests to address their occurrence and impact of foraging on natural habitat. We surveyed the western island with three camera trapping surveys within one year. We found that the species' estimated occupancy probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We identified a cold period (October-March: mean temperature, 9.0 ± 3.0 °C) and a warm one (April–September: mean temperature, 17.0 ± 5.0 °C). We defined activity as the cumulate period that animals spend outside resting sites, regardless of their behavior [ 9 , 62 ]. For all videos, we recorded the date and the solar hour of capture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a cold period (October-March: mean temperature, 9.0 ± 3.0 °C) and a warm one (April–September: mean temperature, 17.0 ± 5.0 °C). We defined activity as the cumulate period that animals spend outside resting sites, regardless of their behavior [ 9 , 62 ]. For all videos, we recorded the date and the solar hour of capture.…”
Section: Methodsmentioning
confidence: 99%
“…The use of camera-traps has provided important ecological information concerning the spatiotemporal behavior of wild species, including species of conservation interest [ 4 ], rare/elusive species [ 5 , 6 , 7 ], as well as problematic species requiring management action such as alien species [ 8 , 9 ]. It has been shown that 30–100 independent camera-trap records per species for each season or year may be sufficient to estimate activity rhythms of wildlife, with results comparable to those obtained from GPS or radio-tracked animals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1) across all habitat types of the study area, in proportion to their local availability. Stations were separated oneanother by at least 500 m (Battocchio et al 2017;Greco et al 2021). Although home range size of the wild boar in Central Italy can be larger in size (Boitani et al 1994;Massei et al 1997), presence of fences around open areas as well as short duration of each camera-trap deployment (14 nights) may have limited the occurrence of the same wild boar groups at different stations during the same deployment (cf.…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
“…Although home range size of the wild boar in Central Italy can be larger in size (Boitani et al 1994;Massei et al 1997), presence of fences around open areas as well as short duration of each camera-trap deployment (14 nights) may have limited the occurrence of the same wild boar groups at different stations during the same deployment (cf. Greco et al 2021). Cameras were distributed in all habitat types, including forest patches and areas over the tree-line level, depending on their accessibility.…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
“…We deployed an artificial nest on the ground at 12 sites, which were separated by at least 300–500 m (Fig. 1), consistent with other studies (Battocchio et al ., 2017; Greco et al ., 2021), to increase independence of records (Holopainen et al, 2020a). Although home range size and ranging movements of the wild boar in Central Italy can include wider areas (e.g., Boitani et al ., 1994; Massei et al ., 1997), presence of fences around some fields as well as the short duration of each deployment (1 week) may have limited the occurrence of the same wild boar groups at different stations during the same deployment.…”
Section: Methodsmentioning
confidence: 99%